Diminished inhibition and facilitated activation of RyR2‐mediated Ca2+ release is a common defect of arrhythmogenic calmodulin mutations. (12th July 2019) - Søndergaard, Mads T.; Liu, Yingjie; Brohus, Malene; Guo, Wenting; Nani, Alma; Carvajal, Catherine; Fill, Michael; Overgaard, Michael T.; Chen, S. R. Wayne
Abstract : A number of calmodulin (CaM) mutations cause severe cardiac arrhythmias, but their arrhythmogenic mechanisms are unclear. While some of the arrhythmogenic CaM mutations have been shown to impair CaM‐dependent inhibition of intracellular Ca 2+ release through the ryanodine receptor type 2 (RyR2), the impact of a majority of these mutations on RyR2 function is unknown. Here, we investigated the effect of 14 arrhythmogenic CaM mutations on the CaM‐dependent RyR2 inhibition. We found that all the arrhythmogenic CaM mutations tested diminished CaM‐dependent inhibition of RyR2‐mediated Ca 2+ release and increased store‐overload induced Ca 2+ release (SOICR) in HEK293 cells. Moreover, all the arrhythmogenic CaM mutations tested either failed to inhibit or even promoted RyR2‐mediated Ca 2+ release in permeabilized HEK293 cells with elevated cytosolic Ca 2+, which was markedly different from the inhibitory action of CaM wild‐type. The CaM mutations also altered the Ca 2+ ‐dependency of CaM binding to the RyR2 CaM‐binding domain. These results demonstrate that diminished inhibition, and even facilitated activation, of RyR2–mediated Ca 2+ release is a common defect of arrhythmogenic CaM mutations. Abstract : Mutations in calmodulin (CaM) cause lethal arrhythmias, and the underlying mechanisms are not fully understood. However, CaM regulation of the cardiac SR Ca 2+ release channel (RyR2) is essential for proper cardiac function. Using HEK293 cells, a CaM‐peptide binding assay and single RyR2 channel experiments we show that the arrhythmogenic mutations generally decrease CaM‐dependent inhibition of RyR2 and can even facilitate RyR2 Ca 2+ release, opposite to the native inhibitory role of CaM.